Peranan Dinas Kebersihan dan Pertamanan dalam Pengelolaan Ruang Terbuka Hijau Di Kota Medan - Aulia Kadri Pratiwi; Beby Masitho Batubara; Irwan Nasution (Universitas Medan Area, 2022)
Medan City is one of the most densely populated cities in Indonesia. The population that is increasing and densely causes a shortage of land. To meet the land needs, many land uses have been converted. One of the impacts of land use conversion is that there is no environmental balance between development and providing green open space. This study aims to determine the roles and obstacles of the Department of Hygiene and Gardening in managing green open spaces in Medan City. This study used a qualitative approach with descriptive methods describing information about the data obtained from the field in the form of written or oral data from the parties studied. Data were collected based on interviews and documentation. The results of this study can be reviewed based on Hardjanto's theory, there are four points, namely: Equality (equality), Consensus Orientation (mutual agreement), Participation (participation), and Responsivenees (responsivity). Based on the research that has been carried out, it is concluded that the role of the Sanitation and Gardening Service in managing green open spaces in Medan City has three roles. First, the preparation of materials for the implementation of the assessment of park development, reforestation and nurseries. Second, the preparation of materials for the preparation of procedures, standards and criteria for the use and management of fields, green open spaces, recreational parks, sports fields, reforestation, urban forests and nurseries. Third, the preparation of materials for coordinating the needs of park, greening and nursery facilities and infrastructure. Meanwhile, the obstacles experienced consist of two obstac les. First, internal obstacles, namely the lack of land to build new public green open spaces, lack of supervision of the construction of private green open spaces, and the lack of socialization on the importance of planting trees. The second is the external obstacle, namely the lack of community participation in building a park or planting trees around the residence.